ANALYSIS OF FACTORS THAT INFLUENCE THE TURNOVER INTENTION OF LAYOFF SURVIVOR EMPLOYEES - Aziz, Rafif Abdul; Desiana, Putri Mega (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2024)
ABSTRACTThis study aims to analyze the influence of job insecurity and perceived organizational support on turnover intention, with employee involvement as a mediating variable. The research sample is employees who experienced layoffs in the 2021-2023. The research was conducted on 163 people who survived layoffs and worked in technology companies. Data collection is done by filling out questionnaires distributed via Google Forms media. The results of this study indicate that job insecurity and perceptions of organizational support have a direct and significant effect on turnover intentions among employees who survive layoffs. Employee involvement also mediates these two variables with turnover intention. This study is expected to help technology companies deal with remaining employees after layoffs. Companies can reduce the possibility of employees wanting to leave the company by increasing employee enthusiasm.ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh job insecurity dan perceived organizational support terhadap turnover intention dengan employee engagement sebagai variabel mediasi. Sampel penelitian adalah karyawan yang tidak mengalami pemutusan hubungan kerja pada periode tahun 2021-2023. Riset dilakukan terhadap 163 layoff survivor yang bekerja di perusahaan teknologi. Pengumpulan data melalui pengisian kuesioner yang disebarkan melalui media Google Forms. Hasil penelitian ini menunjukkan bahwa job insecurity dan perceived organization support berpengaruh langsung dan signifikan terhadap turnover intention pada karyawan yang selamat dari layoff. Employee engagement juga mampu memediasi kedua variabel tersebut dengan turnover intention. Studi ini diharapkan dapat membantu perusahaan teknologi untuk menangani karyawan yang tersisa setelah terjadi pemutusan hubungan kerja. Perusahaan dapat mengurangi kemungkinan karyawan ingin keluar dari perusahaan dengan cara meningkatkan semangat karyawan dalam bekerja.